2018
DOI: 10.1590/1678-4685-gmb-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Comet and cytogenetic tests as tools for evaluating genomic instability in seeds of Oryza sativa L. and Phaseolus vulgaris L. from gene banks

Abstract: This study aimed to assess the feasibility of comet and cytogenetic tests as tools for evaluating genomic instability in seeds of Oryza sativa L. (rice) and Phaseolus vulgaris (beans) L. from gene banks. Rice and beans were exposed to methyl methanesulfonate (MMS) as a reference DNA damaging agent. Seeds of two accessions of rice and beans were obtained from Embrapa Rice and Beans - Brazil. Seed groups were imbibed in three concentrations of MMS for three periods of time to carry out cytogenetic tests, and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Other studies used these buffers supplemented with Na 2 EDTA and with or without DMSO [ 24 , 28 , 51 ]. There are also variations in the composition of the lysis solution used to disrupt the nuclear membrane and protein components [ 23 , 27 , 30 , 43 , 44 ]. Several reports concluded, however, that the lysis step is redundant [ 20 , 21 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies used these buffers supplemented with Na 2 EDTA and with or without DMSO [ 24 , 28 , 51 ]. There are also variations in the composition of the lysis solution used to disrupt the nuclear membrane and protein components [ 23 , 27 , 30 , 43 , 44 ]. Several reports concluded, however, that the lysis step is redundant [ 20 , 21 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies, however, have revealed that DNA damage and repair capacity are also major factors that determine germplasm viability [ 40 ]. Indeed, the loss of genomic integrity is one of the first stages of germplasm deterioration [ 30 ]. Understanding the mechanism of DNA damage and repair, and the development of a method to assess and monitor genome integrity, will improve the application and reliability of ex-situ preservation of plant genetic resources in gene banks.…”
Section: Introductionmentioning
confidence: 99%
“…However, under the influence of environmental and anthropogenic factors, the areas of their growth are decreasing (Schlaepfer et al, 2018;Swift et al, 2019;González et al, 2020;Mayerhofer et al, 2021). In modern genebanks, to preserve plant genetic resources, along with traditional methods, biotechnological ones are successfully used, which include preserving plant germplasm in culture in vitro and cryopreservation at a temperature of -196°C (Dantas et al, 2018;Popova, 2018;Sofi et al, 2020;Özbek and Zencirci, 2021). Cryopreservation of germplasm of plant material in liquid nitrogen guarantees long-term preservation of the material and at the same time reduces the availability of the occurrence of genetic changes possible in in vitro culture at positive temperatures (Jenderek and Reed, 2017;Kalaiselvi et al, 2017;Kaya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The same approach was also used by de Sousa Araujo et al ( 2019 ) to disclose the genotoxic impact of prolonged kinetin-based seed priming in M. truncatula . Genomic instability was evaluated in seeds of rice and beans stored in gene banks using comet assay to investigate the molecular bases of seed deterioration (Dantas et al 2018 ). Comet assay has been tested on embryos or embryo axes isolated from eggplant (Kiran et al 2020 ), M. truncatula (Pagano et al 2022a ), and Acer pseudoplatanus L. (Plitta-Michalak et al 2022 ) seeds.…”
Section: Introductionmentioning
confidence: 99%